The The Effect Of Watermelon Seed (Citrullus Lanatus (Thunb) Mansf.) Ethanol Extract Concentration And Soaking Duration On The In Vitro Dissolution Of Calcium Kidney Stones - Eka Susanti Hanhadyanaputri; Nia Dewi Kumalasari; Agus Suprijono (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Kidney stones are a collection of mineral salts such as uric acid, phosphate, and calcium oxalate that form from substances that accumulate along the urinary tract. Kidney stones can cause pain in the back, waist, and lower abdomen. Therefore, efforts are needed to dissolve kidney stones, one of which is with watermelon seeds. Watermelon seeds contain flavonoids that are thought to be able to dissolve calcium kidney stones. The aims of this research was to determine whether the concentration of watermelon seed extract and the duration of soaking calcium kidney stones can dissolve calcium kidney stones in vitro. The object of the research was the concentration of calcium kidney stones dissolved after the addition of watermelon seed extract. Watermelon seed powder was extracted using a maceration method with 70% ethanol solvent, then make watermelon seed extract concentrations of 2%, 4%, and 6% and the kidney stones were soaked in the watermelon seed ethanol extract concentration for 3 and 5 hours. Analysis of the dissolved calcium kidney stones was measured used the Atomic Absorption Spectrophotometer method. Identification of the type of kidney stone was carried out used an FTIR spectrophotometer. The result research shows that watermelon seed extract with a concentration of 2%, 4%, and 6% can dissolve calcium kidney stones with a 3-hour soaking duration of 24.34 ppm, 69.87 ppm, and 137.06 ppm on average, while a 5-hour soaking duration of 31.61 ppm, 82.27 ppm, and 140.82 ppm on average. Statistical tests show that there is an effect of extract concentration and soaking time of kidney stones in dissolving calcium kidney stones in vitro and the longer the soaking time the larger the kidney stones that can be dissolved